2004
DOI: 10.1172/jci21102
|View full text |Cite
|
Sign up to set email alerts
|

Novel mode of action of c-kit tyrosine kinase inhibitors leading to NK cell–dependent antitumor effects

Abstract: Mutant isoforms of the KIT or PDGF receptors expressed by gastrointestinal stromal tumors (GISTs) are considered the therapeutic targets for STI571 (imatinib mesylate; Gleevec), a specific inhibitor of these tyrosine kinase receptors. Case reports of clinical efficacy of Gleevec in GISTs lacking the typical receptor mutations prompted a search for an alternate mode of action. Here we show that Gleevec can act on host DCs to promote NK cell activation. DC-mediated NK cell activation was triggered in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
186
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(195 citation statements)
references
References 32 publications
(17 reference statements)
4
186
0
2
Order By: Relevance
“…The use of NK cell IFN-g secretion capacity as a surrogate marker for NK cell activity is becoming increasingly popular and has already been designated as a positive prognostic marker in chronic myeloid leukemia 71 and gastrointestinal stromal tumors. 72,73 Also for adult acute leukemia it has been suggested that impaired NK cell cytokine production is associated with early relapse regardless of remission status. 20 Moreover, several recent studies indicate that the potency of NK cells to secrete IFN-g is depressed in AML patients resulting in deprived immune responses (Table 1).…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…The use of NK cell IFN-g secretion capacity as a surrogate marker for NK cell activity is becoming increasingly popular and has already been designated as a positive prognostic marker in chronic myeloid leukemia 71 and gastrointestinal stromal tumors. 72,73 Also for adult acute leukemia it has been suggested that impaired NK cell cytokine production is associated with early relapse regardless of remission status. 20 Moreover, several recent studies indicate that the potency of NK cells to secrete IFN-g is depressed in AML patients resulting in deprived immune responses (Table 1).…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…30 Recent clinical investigations showed that the treatment of patients with Imatinib mesylate (IM/Gleevec s /STI571), an inhibitor of c-kit tyrosine kinase, or with Flt3-L, which induces DC expansion and the DC-mediated NK antitumor effect, is associated with prolonged survival. 48,49 The NK/DC cross talk is bidirectional; NK cells reciprocally trigger and/or sustain maturation of DCs, therefore promoting a T cell-mediated antitumor immune response. The NK-mediated maturation of DCs is based on cell-to-cell contact, especially involving NKp30 and proinflammatory cytokines including TNF-a/ IFN-g (for a complete review see Walzer et al 30 ).…”
Section: Dc-nk Cross Talk Is Center Stage Of Tumor Immuno-surveillancementioning
confidence: 99%
“…IM has already proven its efficiency in the clinic to stimulate the host-dependent antitumor immunity in gastrointestinal stromal tumor patients via the enhancement of DC-mediated NK priming. 48 The adoptive transfer of IKDCs into tumor-bearing immunodeficient mice and TRAIL blocking experiments were the first in vivo evidence of KDC involvement in tumor immunosurveillance. 78 It thus becomes critical to identify the human counterpart of IKDCs and evaluate their antitumor activity in vivo.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…One explanation may be the location of the tumor in the models used, including subcutaneous, skin and lungs, as well as the timing of targeted therapy in relation to immune cell depletion. Similarly, imatinib efficacy is dependent on NK cells in melanoma metastasis models [128], whereas CD8 + T cells contribute to tumor regression following imatinib treatment of GIST-bearing mice or dasatinib treatment of subcutaneous mastocytoma-bearing mice [129,130].…”
Section: Adaptive Immune Cellsmentioning
confidence: 99%
“…TAMs resident in pancreatic tumors suppress CD8 + T cell functions, and targeting TAMs via anti-CSF1R together with gemcitabine decreases liver metastasis through reactivation of CD8 + T cells [29]. Experiments carried out in melanoma metastasis models have shown that the BRAF inhibitor, PLX4720, and the cKIT inhibitor, imatinib, are effective against lung metastases via an NK cell-dependent mechanism [123,128]. In addition, other mechanistic studies have identified several putative targets that may be effective at combating metastasis, including IL17-producing γδ T cells [49] and prometastatic neutrophils [48,49].…”
Section: Glossary Boxmentioning
confidence: 99%